Republic of Madagascar : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2004)
The report reviews the Joint Staff Assessment (JSA) on Madagascar's Poverty Reduction Strategy Paper (PRSP). The full PRSP is built on the interim poverty reduction strategy. The report evaluates both strengths and weaknesses of Madagascar's poverty reduction objectives and strategies, and considers whether the PRSP provides a sound basis for concessional assistance and for debt relief under the Enhanced Heavily Indebted Poor Countries (HIPC) Debt Initiative. The JSA considers Madagascar PRSP as a major accomplishment and provides a sound basis for IMF concessional assistance.